Studi Penggunaan Kapur Tohor Dalam Proses Penetralan Air Asam Tambang Di KPL Pit 3 Barat IUP Tamban Penggunaan Kapur Tohor Dalam Proses Penetralan Air Asam Tambang Di KPL Pit 3 Barat IUP Tambang Banko Barat PT Bukit Asam Tbk Tanjung Enim Sumatera Selatan - Ester Indah Sari; E.P.S.B Taman Tono; Guskarnali Guskarnali (MINERAL, 2018)
The process of acid mine drainage in settling pond Pit 3 Barat Banko Barat PT Bukit Asam Tbk uses quicklime for berries carried out in the first inlet or pond channel. The pH value after the neutralization process has fulfilled the environmental quality standard value of 6-9 but the use of quicklime is less effective because it does not match the amount of water in the settling pond Pit 3 Barat Banko Barat. This can affect the economic use of quicklime in the Settling Pond. Therefore, testing and recalculation are needed in order to know the amount of quicklime to neutralize acid mine drainage and the cost of using lime needed based on the volume of water in the settling pond. The actual data in the field for the use of quicklime is 0.4 gr / l to be able to centralize acid mine drainage in accordance with environmental quality standards. This research method is testing 13 samples of acid mine neutralizing water in the laboratory with the addition of quicklime in order to calculate the amount of quicklime and the cost of using quicklime which is needed to neutralize acid mine drainage. Test results in the laboratory obtained a dose of quicklime of 0.2 gr / l to be able to neutralize the water to fit Environmental Quality Standards with an initial pH value of 3.43 to 7.11 after adding quicklime. The volume of water used is the settling pond volume which is 3,600,000 l. The amount of quicklime needed after testing in the laboratory is 18 sacks, while the actual amount of quicklime used in the field is 36 sacks. The actual cost required in using lime based on data in the field is Rp 1,224,000.00 and the cost of using quicklime based on laboratory testing data is Rp 612,000.00